THE EFFECT OF DIVIDEND POLICY AND LEVERAGE ON FIRM VALUE: THE MODERATING ROLE OF AUDIT QUALITY - Ayudya Arifatur Niza; Lu'lu' Nafiati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
This study analyzes the effects of dividend policy and leverage on firm value, with audit quality as a moderating variable. The sample includes manufacturing firms listed on the Indonesia Stock Exchange from 2015 to 2024. Using a quantitative panel data approach and the random effects model on 67 firm-year observations, the study employs multiple regression and moderation analyses to examine direct and interaction effects. Results show that both dividend policy and leverage positively and significantly affect firm value, highlighting the importance of financial signaling and optimal capital structure in emerging markets. Importantly, audit quality, proxied by Big Four auditor engagement, strengthens the positive link between dividend policy and firm value. This underscores the role of high-quality audits in enhancing financial signal credibility and reducing information asymmetry. However, audit quality does not significantly moderate the leverage–firm value relationship, indicating complexities in managing debt risk. This research advances prior literature by combining financial policies and audit quality in one framework within an underexplored emerging market. The findings offer practical guidance for managers and regulators to leverage audit quality as a strategic means to increase investor confidence and firm valuation in developing economies.